2016
DOI: 10.1007/s11258-016-0620-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decomposition of Quercus mongolica branches

Abstract: Litter decomposition is a critical process for the maintenance of terrestrial ecosystems. Although large quantities of organic matter and nutrients are supplied by branch litter, its decomposition has received little attention. In this study, we focused on Quercus mongolica, one of the most common temperate deciduous woody species in the Northern Hemisphere, to investigate the age-related decomposition rate of branches. Branches of different age classes (2, 4, 7, 10, and 13 years), downed after a summer windst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Within the coniferous tree stands, an average SOC of 3.63% ± 1.49% was recorded: Larix principallis from Northeast China had the maximum (6.16%) (Miao et al 2013) and Juneperus excelsa from Northern Pakistan, had the least (0.70%) (Shedayi et al 2016). In deciduous tree stands, which had an average SOC of 3.14% ± 1.70%, Fagus sylvatica had the maximum (8.4%) (Kooijman et al 2009) followed by Betula utilis (7.57%) (Shedayi et al 2016), Quercus mongolica (6.9%) (Chae et al 2016), Betula platyphylla (6.8%) (Miao et al 2013) and Dipterocarpus tuberculatus had the least (0.2%) (Yadava and Devi 2007). In evergreen tree stands, the maximum SOC level was 7.37% in Leuceana leucocephalla (Marler et al 2016), followed by 6.8% in Castanopsis fargesii (Si et al 2018), and the minimum level was 0.32% in Casuarina equisetifolia (Panda 2020); the average was 3.28% ± 1.66%.…”
Section: Resultsmentioning
confidence: 96%
“…Within the coniferous tree stands, an average SOC of 3.63% ± 1.49% was recorded: Larix principallis from Northeast China had the maximum (6.16%) (Miao et al 2013) and Juneperus excelsa from Northern Pakistan, had the least (0.70%) (Shedayi et al 2016). In deciduous tree stands, which had an average SOC of 3.14% ± 1.70%, Fagus sylvatica had the maximum (8.4%) (Kooijman et al 2009) followed by Betula utilis (7.57%) (Shedayi et al 2016), Quercus mongolica (6.9%) (Chae et al 2016), Betula platyphylla (6.8%) (Miao et al 2013) and Dipterocarpus tuberculatus had the least (0.2%) (Yadava and Devi 2007). In evergreen tree stands, the maximum SOC level was 7.37% in Leuceana leucocephalla (Marler et al 2016), followed by 6.8% in Castanopsis fargesii (Si et al 2018), and the minimum level was 0.32% in Casuarina equisetifolia (Panda 2020); the average was 3.28% ± 1.66%.…”
Section: Resultsmentioning
confidence: 96%
“…In other studies, the k values for each individual pine species ranged from 0.108 to 0.256 for P. densiflora [38,40], 0.148 to 0.400 for P. koraiensis [38,41,46], 0.191 to 0.262 for P. rigida [38,39,41], and 0.133 to 0.177 for P. thunbergii [38]. Previous studies indicated that decomposition varies between species and is affected by physical and regional factors [56]. Although the decomposition rate in our study was similar to that observed by You et al [42] for P. koraiensis (k value: 0.40) and P. rigida (k value: 0.37) in a planted pine forest [42], the study was not conducted to reveal significant relationships between the degradation rate and litter quality.…”
Section: Difference In Decomposition Rate Between Pine Speciesmentioning
confidence: 99%
“…Wolbachia is an important endosymbiont commonly observed in the microbiota of arthropods and plays an essential role in regulating the reproductive behavior of the host ( Czarnetzki and Tebbe, 2004 ; Werren et al, 2008 ). The C:N ratio of food greatly affects the reproduction of Collembola ( Larsen et al, 2008 ); Previous studies reported that mongolian oak litter has a high C:N ratio, compared to the corn litter ( Chen et al, 2003 ; Chae et al, 2016 ). The mongolian oak litter with high C:N ratio was found to result in a high proportion of Wolbachia in cold-adapted Collembola, and it could therefore be hypothesized that a poor food source can make Collembola more susceptible to the infection, thus relative abundance of Wolbachia will increase.…”
Section: Discussionmentioning
confidence: 99%